Perlindungan Hukum Ojek Online dalam Perspektif Hukum Pengangkutan di Indonesia - Priska Evelyn; Utiyafina Mardhati Hazhin (Darma Cendika Catholic University, 2025)
Technological advancements have transformed various aspects of life, including transportation. One of the innovations in this field is online motorcycle taxis, which offer convenience to the public through app-based services. However, despite their benefits, online motorcycle taxis face several challenges, particularly in legal and regulatory aspects. Some regions have even temporarily banned their operations due to the lack of recognition as public transportation under Law Number 22 of 2009 concerning Road Traffic and Transportation. This study aims to analyze the legal position and protection of online motorcycle taxis from the perspective of transportation law in Indonesia. The research employs a normative juridical approach and literature study. The findings indicate that online motorcycle taxis fulfill the concept of transportation, which involves the movement of passengers or goods using a means of transport. However, since motorcycles are not categorized as public transport under existing regulations, online motorcycle taxis lack a strong legal foundation. The issuance of Minister of Transportation Regulation Number 12 of 2019 provides a legal basis for their operation and offers legal protection for drivers and passengers. Nonetheless, more comprehensive regulations are still needed to ensure legal certainty and better protection for all parties involved in online motorcycle taxi services